A Novel Role for miR‐1305 in Regulation of Pluripotency‐Differentiation Balance, Cell Cycle, and Apoptosis in Human Pluripotent Stem Cells. (11th July 2016) - Jin, Shibo; Collin, Joseph; Zhu, Lili; Montaner, David; Armstrong, Lyle; Neganova, Irina; Lako, Majlinda
Abstract : Human embryonic stem cells (hESCs) and human induced pluripotent stem cells (hiPSCs) are defined as pluripotent in view of their self‐renewal ability and potential to differentiate to cells of all three germ layers. Recent studies have indicated that microRNAs (miRNAs) play an important role in the maintenance of pluripotency and cell cycle regulation. We used a microarray based approach to identify miRNAs that were enriched in hESCs when compared to differentiated cells and at the same time showed significant expression changes between different phases of cell cycle. We identified 34 candidate miRNAs and performed functional studies on one of these, miR‐1305, which showed the highest expression change during cell cycle transition. Overexpression of miR‐1305 induced differentiation of pluripotent stem cells, increased cell apoptosis and sped up G1/S transition, while its downregulation facilitated the maintenance of pluripotency and increased cell survival. Using target prediction software and luciferase based reporter assays we identified POLR3G as a downstream target by which miR‐1305 regulates the fine balance between maintenance of pluripotency and onset of differentiation. Overexpression of POLR3G rescued pluripotent stem cell differentiation induced by miR‐1305 overexpression. In contrast, knock‐down of POLR3G expression abolished the miR‐1305‐knockdown mediated enhancement of pluripotency, thus validating its role as miR‐1305 target in human pluripotent stem cells. Together our data point to an important role for miR‐1305 as a novel regulator of pluripotency, cell survival and cell cycle and uncovers new mechanisms and networks by which these processes are intertwined in human pluripotent stem cells. Stem Cells 2016;34:2306–2317